Alterations in masticatory cycle efficiency and bite force in individuals with periodontitis - Palinkas, Marcelo; Borges, Tânia de Freitas; Junior, Mario Taba; Monteiro, Solange Aparecida Caldeira; Mestriner-Junior, Wilson; Regalo, Isabela Hallak; Siéssere, Selma; Semprini, Marisa; Regalo, Simone Cecilio Hallak (International Journal of Health Sciences, 2018)
Objectives: The objective of this research was to evaluate the effect of periodontitis on masticatory cycle efficiency and maximum molar bite force. Methods: Twenty-four individuals were divided into two groups: With periodontitis (Group I; mean age ± standard deviation (SD), 51.3 ± 2.8 years; n = 12) and without periodontitis (Group II; mean age ± SD, 48.9 ± 2.4 years; n = 12). Masticatory cycle efficiency was obtained from the value of the ensemble-averaged integrated linear envelope electromyographic signal of the masseter and temporalis muscles. Maximum bite force was recorded for the right and left molar regions. The data were tabulated and submitted to statistical analysis (P ≤ 0.05). Results: There was a significant difference between the groups for the left masseter muscle when chewing raisins (P = 0.04), peanuts (P = 0.02), and biocapsules (P = 0.01). Multiple regression analysis demonstrated the influence of dental mobility on masticatory cycle efficiency for peanuts (P = 0.03) and biocapsules (P = 0.01). The maximum bite force for the left molar region was significantly different between the groups (P = 0.02). Dental mobility was a variable that had a greater effect on masticatory cycle efficiency. The periodontitis group had a reduced bite force. Conclusion: The present study findings indicate that the loss of periodontal supporting structures had a negative impact on masticatory cycle efficiency and molar bite force. This finding suggested that dental mobility should be considered when determining clinical treatments aimed at improving masticatory efficiency and bite force in individuals with the periodontal disease.